Synthesis of Zinc Oxide (ZnO)-Titanium Dioxide (TiO2)-Chitosan-Farnesol Nanocomposites and Assessment of Their Anticancer Potential in Human Leukemic MOLT-4 Cell Line. (28th September 2022) - Elderdery, Abozer Y.; Alzahrani, Badr; Hamza, Siddiqa M. A.; Mostafa-Hedeab, Gomaa; Mok, Pooi Ling; Subbiah, Suresh Kumar
Abstract : Leukemia is the most prevalent cancer in children and one of the most common and deadly cancers that affect adults. Several metal oxide nanoparticles, biopolymers, and phytochemicals have been discovered to target cancer cells selectively while inflicting low to no damage to healthy cells. Among the existing nanoparticle synthesis methodologies, biologically synthesized nanoparticles using phytochemicals have emerged as a straightforward, economical, and environmentally sound strategy. The synergistic antitumor potential of ZnO-TiO2 -chitosan-farnesol nanocomposites (NCs) against leukemia MOLT-4 cells was investigated in the current study. After synthesizing the NCs, characterization of the same was carried out using XRD, DLS, FESEM, TEM, PL, EDX, and FTIR spectroscopy. To analyze its anticancer activity, MOLT-4 cells were cultured and treated at diverse dosages of NCs. The cell viability upon treatment was examined by MTT assay. The morphological and nuclear modifications were observed by dual staining. ROS and MMP levels were observed by DCFH-DA staining and Rh-123 dye, respectively. Furthermore, the caspase 3, 8, and 9 levels were examined by performing ELISA. The XRD patterns exhibited a hexagonal structure of the NCs. In the DLS spectrum, the hydrodynamic diameter of the NCs was observed to be 126.2 nm. The electrostatic interface between the ZnO-TiO2 -chitosan-farnesol NCs was confirmed by the FTIR spectra. A significant loss of cell viability in a dosage-dependent trend confirmed the cytotoxic effect of the NCs. An elevated ROS level and MMP depletion suggested apoptosis-associated cell death via the intrinsic pathway, which was confirmed by elevated expressions of caspase 3, 8, and 9 markers. Thus, the results showed that the synthesized NCs demonstrated a remarkable anticancer potential against leukemic cells and can be potentially valuable in cancer treatments. The findings from this study conclude that this is a new approach for modifying the physicochemical characteristics of ZnO-TiO2 -chitosan-farnesol composites to increase their properties and synergistically exhibit anticancer properties in human leukemic cancer cells.